Eficiência do uso do N no sistema de manejo de leguminosas consorciadas à pastagem em solos arenosos - Moreira, Ana Carolina Mônico (2021)
Nitrogen is considered an essential element for the development and growth of plants, but it is difficult to manage due to its high mobility in the soil that leads to greater losses by leaching, volatilization and denitrification. These losses can be more intense in sandy soils with low content of clay and organic matter. The great challenge from this is to accumulate organic matter in sandy textured soils to improve the conditions of the production system. The objective of the work was to quantify the improvement of the environment (soil) of crop growth in a crop-livestock integration system, with the supply of N through fertilization in cover or intercropping with legumes in pasture areas. The experiment was installed at the Experimental Farm of the Universidade do Oeste Paulista - UNOESTE, in Presidente Bernardes-SP, in a soil classified as red-yellow dystrophic argilúvico Latosol (EMBRAPA, 2006). The experimental design was defined in randomized blocks, with four replications: 1) Guinea grass (Panicum maximum cv. Mombaça) single with nitrogen fertilization cover; 2) Guinea grass intercropped with dwarf pigeon pea (Cajanus cajan) without nitrogen fertilization; 3) Guinea grass without nitrogen top dressing and; 4) Guinea grass intercropped with Macrotyloma axillare cv. Java without nitrogen fertilization. Chapter 1: N-total and N-inorganic (N-NH4+ and N-NO3-) contents of the soil, COS content and C and N levels of microbial biomass were evaluated. Chapter 2: the volatilization rate of N-NH3 in the soil and the system (soil + plant) was evaluated. E Chapter 3: the accumulation of N-NH4+ and N-NO3- from the Mombasa leaf and the production of dry biomass was evaluated.